É que pra mim vocês são invisíveis: relações de gênero em aulas de ciências do ensino fundamental - Freitas, Lucas Bueno de (2019)
The aim of this paper is to analyze the manifestations of gender stereotypes, based on patriarchal culture, on the relationship between girls and boys in the daily science classes of the 4th and 5th grade of elementary school in a municipal school in Pinhais - PR. This objective was delimited from one problem: the lower number of women in scientific and technological professions. Of the different possible approaches to explaining this numerical difference, I opted for elementary school, when children are not yet defining their professional future, but are in the early stages of the learning process that will culminate in such a definition. The methodology chosen for the research was the qualitative approach, adopting methods of ethnographic studies. After choosing the school for the research, a questionnaire was conducted with the children, to know the professional reality of their families, their professional dreams and identify the children's imaginary about a person who works as a scientist. After a year of ethnography I chose four categories for analysis: the first is an analysis of how gender representations are manifested by children; the second is the analysis of the interaction of these representations with scientific knowledge under the teacher's ministry and guidance; the third analyzes this gender relationship during the group work proposed by science teachers, in which children have greater freedom and self-management of knowledge; the fourth and final category will analyze the confrontations and resistances expressed by girls. The thesis obtained after the research is that patriarchy interferes with the teaching-learning process of girls, with patterns and stereotypes that are not consistent with the development of scientific knowledge.